Tears and transformation: feeling like crying as an indicator of insightful or “aesthetic” experience with art - Pelowski, Matthew J. (Frontiers in Psychology, 2015)
This paper explores a fundamental similarity between cognitive models for crying and conceptions of insight, enlightenment or, in the context of art, “aesthetic experience.” All of which center on a process of initial discrepancy, followed by schema change, and conclude in a proposed adjustment or “transformation” of one's self image/world-view. Because tears are argued to mark one of the only physical indicators of this cognitive outcome, and because the process is particularly salient in examples with art, I argue that crying may provide an intriguing marker for empirical study of art experience. To explore this parallel, I offer a review of crying theory as well as of tearful cases with art, pointing out the key cognitive elements. I then introduce an expanded crying model, based upon our recent model of art experience which does consider insight and adjustment or application of the self. I also consider multiple emotional and evaluative factors, which may co-vary with crying response. This theoretical discussion is then applied in three exploratory, survey-based studies conducted within U.K., Japan and U.S. museums, and including what is claimed to be the 20th century's most tear-inducing abstract paintings. Results showed—with cross-cultural consistency—significant relation between “feeling like crying” and a collection of responses posited to indicate a full progression to aesthetic experience, as well as to positive assessment of artwork goodness, beauty, understanding of meaning, and to final reported self reflection and epiphany. I argue that, beyond the question of why we may cry, by considering the implications of what tears may indicate within information processing, feeling like crying may indeed offer a compelling basis for empirically identifying outcomes of perceptual (art) experience.